Games, Ideas and Activities for Primary Modern Foreign Languages - Drinkwater, Nicola (New Dehli Pearson, 2014)
Description This new book embodies the philosophy of learning through play. It aims to equip those faced with teaching foreign languages in the primary sector with a large collection of classroom activities which encourage pupils to use the foreign language in a fun and physical way, while focusing on speaking skills. Readers are given background into how to use the activities effectively, how to combine activities in one lesson and how to adapt activities to suit different age groups to ensure they get the most out of their lessons
Include Illustrations
Keywords: Drinkwater, Nicola